Effect of oestrus cervical mucus peroxidase and fern pattern on fertility in crossbred cows - SRIVASTAVA, S K; SHANKER, UMA; AGARWAL, S K; SAHNI, K L (The Indian Journal of Animal Sciences, 2014)
Cervical mucus peroxidase activity and ferning pattern was studied in 60 crossbred cows at the AI, Typical (63.33%), atypical (26.67%) and nil (10.00%) types of pattern were observed. After insemination and pregnancy diagnosis 55.26% and 18.77% cows became pregnant with typical and atypical types of patterns which were significantly different (P<0.05). Peroxidase activity was estimated in mucus samples of same cows and were categorized in 3 groups (less than 0.15u-g; 0.16 to 0.30ug, and more than 0.30 ug). In above 3 groups conception rate was 66.66, 45.00 and 14.28%, respectively. Thus, CMP affected pregnancy significantly. Study were also carried out to know the relationship between pregnancy and colour intensity developed owing to peroxidase. Pregnancy with no colour and light colour intensity was 50.00% and with moderate colour 30.77%. Pregnancy reduced with dark colour intensity. Thus, CMP colour intensity also have relationship with pregnancy.